Rancangan Aplikasi Monitoring Online Untuk Meningkatkan Pemeliharaan Prediktif Pada PLTD - Paillin, Daniel Bunga; Widiatmoko, Yoyok (JSINBIS (Jurnal Sistem Informasi Bisnis), 2021)
Evaluation of operating data is one of the most important things about preventing disruption to the diesel generating unit. At this time process of recording the condition of the power plant (log sheet) in PLTD Hative Kecil is still done manually so that the evaluation process of the data that has been taken is still not optimal, and the use of parameter data as a basis for improving engine performance has also not been maximized. The purpose of this study is to design a web-based plant operation monitoring application to optimize predictive maintenance, improve the efficiency and effectiveness of processing plant data operations and as a reference for maintenance planning and assist in making decisions so that Operational Excellence can be achieved. The results of the design can provide information on the condition of the engine in real-time that can be used for planning, controlling, and evaluating the predictive maintenance of diesel generators in PLTD Hative Kecil